1988
DOI: 10.1007/bf00195363
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro investigations on biological effects of aromatic bis-(2-chloroethyl)amino-bisphosphonic acids, new agents proposed for chemotherapy of bone tumors: cytostatic activity in rat osteosarcoma; toxicity and genotoxicity in liver and bone marrow; mutagenicity in S. Typhimurium

Abstract: Two new aromatic bis-(2-chloroethyl)-amino derivatives (BCMP and BAD) which are linked to osteotropic bisphosphonates were investigated for their therapeutical efficacy in rat osteosarcoma. Furthermore their genotoxic potential in vitro was determined in S. typhimurium and in mammalian cells. Finally, parameters for toxicity and genotoxicity were determined in liver and bone marrow cells following in vivo treatment. It was shown that BAD was of higher therapeutic effectiveness than BCMP. Both compounds induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…13 3-[Bis-(2-chloroethyl)-amino]-4-methylphenylhydroxymethane-1,1-bisphosphonic acid (BCMP), a derivative of BAD, had a lower cytostatic activity than BAD alone against rat osteosarcoma, and as a result it was not further investigated. 14 Keppler et al prepared a bisphosphonate cisplatin-analogue in which a phosphonate is complexed with diaminoplatinum (cis-diammine[nitrilotris(methylphosphonato)(2)-O 1 ,N 1 ]platinum(II), AMDP). 15 The therapeutic efficacy of this complex was better than pamidronate but not superior to conventional cisplatin in a transplantable osteosarcoma model of the rat, even at a 28-fold higher dose.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 3-[Bis-(2-chloroethyl)-amino]-4-methylphenylhydroxymethane-1,1-bisphosphonic acid (BCMP), a derivative of BAD, had a lower cytostatic activity than BAD alone against rat osteosarcoma, and as a result it was not further investigated. 14 Keppler et al prepared a bisphosphonate cisplatin-analogue in which a phosphonate is complexed with diaminoplatinum (cis-diammine[nitrilotris(methylphosphonato)(2)-O 1 ,N 1 ]platinum(II), AMDP). 15 The therapeutic efficacy of this complex was better than pamidronate but not superior to conventional cisplatin in a transplantable osteosarcoma model of the rat, even at a 28-fold higher dose.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although it showed a higher anticancer activity than monotherapy with either melphalan or pamidronate in N -methyl- N -nitrosourea induced mammary carcinomas in Sprague–Dawley rats, a combination therapy of pamidronate and melphalan showed the best therapeutic efficacy in this tumor model . 3-[Bis-(2-chloroethyl)-amino]-4-methylphenyl-hydroxymethane-1,1-bisphosphonic acid (BCMP), a derivative of BAD, had a lower cytostatic activity than BAD alone against rat osteosarcoma, and as a result it was not further investigated …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the negative findings in our model system using SV40 transformed cells may be important not only for the lacking potential carcinogenic effects, rather the results may indicate also a lacking potential of the resistance phenomena by the mechanism of DNA amplification. In contrast BAD had been shown to be active in the assay for amplification [37]. Therefore the activities reported there and the findings on the genotoxicity of melphalan reported by others [38], indicate that when BAD is detectably genotoxic, it is probably due to its melphalan-acting moiety and not to the APD part of the molecule.…”
Section: Discussionmentioning
confidence: 58%
“…68 Some researchers have examined the effects of bisphosphonates on osteosarcoma cell lines. 28,49,[69][70][71][72][73][74] Some indication exists that the amino-bisphosphonate pamidronate may be more effective than clodronate in inhibiting cell growth in these cell lines. 69 Research also has shown that marked synergy exists when bisphosphonates are combined with chemotherapy drugs such as taxanes, doxorubicin, dexamethasone, and cyclooxygenase 2 inhibitors.…”
Section: Inhibition Of Tumor Cell Proliferation and Induction Of Apopmentioning
confidence: 99%